A dynamic theory of random price discounts - Francesc Dilmé; Daniel F. Garrett (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
A seller with commitment power sets prices over time. Risk-averse buyers arrive to the market and decide when to purchase. We obtain that the optimal price path is a "regular" price, with occasional episodes of sequential discounts that occur at random times. The optimal price path has the property that the price a buyer ends up paying is independent of his arrival and purchase times, and only depends on his valuation. Our theory accommodates empirical findings on the timing of discounts.
Keywords: D82; 330; dynamic pricing; sales; random mechanisms